Mathematical modeling of ephemeral gully erosion - Karimov, Vladimir Rustemovich (Kansas State University, 2017)
As the world faces an increasing demand for food due to the growing global population and the pernicious effects of land degradation, there is a need to overcome this challenge by using sustainable management practices for agricultural productions. One of the problems, which sustainable agriculture seeks to address, is the loss of topsoil due to soil erosion. Changing weather patterns also contribute to the average annual rainfall across the globe with an excess precipitation, which creates runoff and causes soil erosion. One of the significant yet less studied types of soil erosion is ephemeral gully erosion. Formed by the concentrated overland flow during intensive rainfall events, ephemeral gullies are channels on agricultural fields that can be removed by tillage operations but appear at the same location every year. Even though simplified ephemeral gully models estimate soil losses, they do not account for complicated hydrological and soil erosion processes of channel formations. The purpose of this research work is to investigate sediment sources and develop tools that can predict ephemeral gully erosion more efficiently. To achieve this goal, an experimental study was conducted on an agricultural field in central Kansas by tracking channel development, monitoring soil moisture content, and recording the amount of rainfall. Runoff and sediment loads from contributing catchment and critical and actual shear stresses were estimated by the computer model, and conclusions were made on the effect of saturation dynamics on the erosion processes. Furthermore, a two-dimensional subsurface water flow and soil erosion model was developed with the variable soil erodibility parameters which account for the subsurface fluxes and the effects on the soil detachment process. The model was applied to study the impacts of variable soil erodibility parameters on the erosion process for different soils and various antecedent soil moisture conditions. Also developed to estimate the soil losses at the field scale was an integrated spatially-distributed ephemeral gully model with dynamic time-dependent channel development. The model showed good fit by matching the experimental data. The results from this work can be used to advance the research of soil erosion prediction from concentrated flow channels and ephemeral gullies formed on agricultural fields.
Keywords: Soil erosion; Erosion modeling; Ephemeral gully; Hydrological modeling; Subsurface hydrology; Critical shear stress